A single-center United States experience with bleeding Dieulafoy lesions of the small bowel: diagnosis and treatment with single-balloon enteroscopy - Lipka, Seth; Rabbanifard, Roshanak; Kumar, Ambuj; Brady, Patrick (Endoscopy International Open, 2015)
Introduction: A Dieulafoy lesion (DL) of the small bowel can cause severe gastrointestinal bleeding, and presents a difficult clinical setting for endoscopists. Limited data exists on the therapeutic yield of treating DLs of the small bowel using single-balloon enteroscopy (SBE). Methods: Data were collected from Tampa General Hospital a 1 018-bed teaching hospital affiliated with University of South Florida in Tampa, Florida. Patients were selected from a database of patients that underwent SBE from January 2010 – August 2013. Results: Eight patients were found to have DL an incidence of 2.6 % of 309 SBE performed for obscure gastrointestinal bleeding. 7/8 were identified in the jejunum, with one found in the duodenum. The mean age of patients with DL was 71.5 years old. 6/8 patients were on some form of anticoagulant/antiplatelet agent. The primary modality of therapy employed was electrocautery, multipolar electrocoagulation in seven patients and APC (argon plasma coagulation) in one patient. In three patients, electrocoagulation was unsuccessful and hemostasis was achieved with clip placement. Three patients required repeat SBE with one found to have rebleeding from a failed clip with hemostasis achieved upon reapplication of one clip.Conclusion: In our United States’ experience, SBE offers a reasonable therapeutic approach to treat DL of the small bowel with low rates of rebleeding, no adverse events, and no patient requiring surgery.